Floristics of Virginia’s Northern and Central Piedmont grasslands - Jordan T. Coscia; J. Berton C. Harris; Devin Floyd; Michael C. Beall; David Bellangue; Drew Chaney; Jared Gorrell; Evie Sackett; Ezra J. Staengl; J. Leighton Reid (Vegetation Classification and Survey (VCS))
Aims: The grasslands of the North American Piedmont host diverse communities of sun-loving plants, but more than 90% of these grasslands have been lost across the region. Grasslands of the northern and central Piedmont of Virginia have received little formal study, but they are likely to be as diverse and threatened as they are in other parts of the eastern United States. To conserve the remaining Piedmont grasslands, we need to characterize floristic communities, identify the edaphic factors and disturbance regimes that drive their persistence, and develop methods to restore degraded grasslands. Study Area: Northern and Central Virginia Piedmont, USA. Methods: We surveyed plant communities and collected soil samples in 132 grasslands in old fields, powerline clearings, and roadsides. We used cluster analysis, indicator species analysis, and non-metric multidimensional scaling overlaid with soil and environmental variables to identify community groups. Results: We identified 695 plant taxa (87% of which are native) including 13 species that are rare in Virginia, two of which are globally critically imperiled (Pycnanthemum clinopodioides and P. torreyi). Six of our study sites contained 100 or more species with a maximum of 114 species in a single plot, making them among the most species-rich 100 m2 plots recorded in the United States. Cluster analysis and ordination indicated four community groups, which we refer to as the Northern Prairies, Central Prairies, Savanna/Woodlands, and Wet Grasslands. Conclusions: The descriptions of these community groups can be used as reference information to inform grassland restoration in Virginia. Virginia’s Piedmont grasslands are threatened by fire suppression, development, invasive species, and inappropriate management by utility companies. Swift action to conserve high quality grasslands and restore degraded ones is required to save these diverse plant communities. Taxonomic reference: Weakley et al. (2012). Abbreviations: NMDS = non-metric multidimensional scaling; PERMANOVA = permutational multivariate analysis of variance.